ANALISIS KORELASI GENETIK ANTARA BOBOT INDUK DAN BOBOT ANAK SAPI PERANAKAN ONGOLE DAN SIMMENTAL PERANAKAN ONGOLE - Nurliani Erni; Teguh Rafian (Jurnal Agriovet, 2025)
This research was conducted to analyze the genetic correlation between dam weight calf weight of Ongole Grade (PO) and Simmental Ongole Grade (SIMPO) cows. This study used 19 Ongole Grade and 37 Simmental Ongole Grade calves and cows. Observed variables included dam weight at calving, calf sex, birth weight, dam weight at weaning, weaning weight, dam weight loss, and calf weight gain. The data were analyzed using Pearson's correlation analysis to estimate the genetic correlation values. The results showed that dam weight at calving, calf birth weight, dam weight at weaning, weaning weight, dam weight loss, and calf weight gain in both PO and SIMPO cattle did not show significant differences between different sexes. Based on the genetic correlation analysis, it was concluded that there was a weak (negative) to moderate (positive) relationship between dam weight and calf weight in PO cows, and a weak (positive) to moderate (negative) relationship in SIMPO cows.